Sensitization of Er3+ Emission in Er- and Yb-doped Si Thin Films by Laser Ablation - Kawai, Shinji (International Conference on Plasma Surface Engineering, 2013)
Erbium (Er)- and ytterbium (Yb)-doped Si (Si:Er,Yb) thin films have been controllably synthesized over the Er and Yb concentrations ranging from 1018 to 1020 cm-3 by laser ablation technique. From the PL spectra and the concentration dependence of the intensity of Er3+ emission at 1.54 µm, Yb3+ acts as an efficient sensitizer of the Er3+-related PL. Enhancement by a factor of 1.5 due to Yb codoping is observed from the Si:Er,Yb films.